Paraganglial cells of urinary bladder and prostate: potential diagnostic problem. Issue 1 (January 1990) - Rode, J; Bentley, A; Parkinson, C
Abstract : A transurethral prostatic resection for prostatism in a 73 year old man showed a cluster of richly capillarised clear cells originally thought to be indicative of invasive carcinoma. Immunohistochemical studies were carried out on this tissue specimen and three similar cases using a variety of antibodies–Neuron specific enolase, PGP 9.5, chromogranin, synaptophysin, serotonin, somatostatin, substance P, calcitonin, calcitonin gene related peptide, met-enkephalin, VIP, neurofilament, CAM 5.2, S100 protein, prostatic specific antigen and prostatic acid phosphatase. The cellular foci were shown to be composed of paraganglionic cells. The cell clusters were well defined and predominantly comprised clear cells with scanty, fine eosinophilic cytoplasmic granules in three cases. The cell nuclei were round to oval, moderately pleomorphic, with evenly dispersed dense chromatin. It is concluded that the presence of minute foci of paraganglial cells in the bladder wall and prostate gland may be misinterpreted as malignant because of their close association with nerves and their relative rarity. Immunohistochemical staining with neuroendocrine markers should dispel any doubt about their identity.